(untitled) (Bangladesh Journal of Botany, 2019)
To develop a simple and reliable inoculation technique using inoculum sources viz., mycelial suspension, mycelial ball, sclerotia and soil inoculation with homogenized mycelia suspension was carried out. The efficiency of different inoculation techniques were tested on susceptible rice variety Rejendra Sweta. Sheath inoculation with sclerotia gave lesion length 10.33 and 12.33 cm after seven and 15 days of inoculation, respectively. It also shows more significance in terms of relative lesion height to plant height i.e. 30.06 % followed by soil inoculation with homogenized mycelial suspension i.e. 21.62 %. However, relative number of lesions as compared to control was found to be maximum (429.18%) in mycelial suspension spray, followed by soil inoculation using homogenized mycelia suspension (400.43%). The disease rating of sheath blight of rice was also found to be maximum (5) in sheath inoculation with sclerotia followed by soil inoculation of mycelial suspension (3). The disease rating was minimum (1) in sheath inoculation with mycelial ball and foliar spray with mycelial suspension.